A quasi-active negative stiffness damper for structural vibration control under earthquakes. (1st July 2022) - Li, Huan; Li, Jianchun; Bi, Kaiming
Highlights: Proposed a novel Quasi-Active Control (QAC) concept. QAC enables a system to closely achieve active-control performance. Illustrated QAC with an example of Quasi-Active Negative Stiffness Damper (QANSD). Developed a generalized approach for analyzing and designing the proposed QANSD. Abstract: This paper proposes a novel quasi-active negative stiffness damper (QANSD) for effective and robust seismic protection. By integrating the negative stiffness element and controllable damping element together, the proposed device enables to closely achieve active control performance with much less energy to operate compared to an active control system. Such a control system has been named as "Quasi-Active" control (QAC) in this study. To introduce the concept of QAC, this paper reiterates the fundamentals of active and semi-active vibration control systems from the perspective of control force, and numerically examines a few examples via comprehensive evaluation indices. The inherent shortfall of semi-active methods on control effectiveness is illustrated by an example of semi-active dampers. It is clearly revealed that the incapacity of semi-active control to capture the entire required active control force (RACF) is due to the fact that the amount of control force that can be generated by a semi-active control system is based on the responses of the structure, which prevents the semi-active control to achieve equivalent active control performance. To address this issue, this paper introduces the QAC concept and a specific realization, i.e. QANSD, including its principles, control strategy and realization. Furthermore, a generalized design approach and related formulae for designing the QANSD are developed with a special interest in obtaining its negative stiffness thresholds. Moreover, to demonstrate its control effectiveness and superiorities, comparative numerical studies are conducted based on a three-storey frame model. The comparisons are made among the same structure without control, with active control, semi-active control, passive control, as well as QAC. In the study, four scaled earthquakes are used as ground motion excitations and five evaluation criteria are adopted to assess the control performances. The results show that, with much less required energy, the QANSD is capable of completely producing RACF and its performance highly matches with the active control performance. Both of them can achieve similar inter-storey drift and displacement suppression effects as semi-active control, but much more evident acceleration and structural shear mitigation performance.